Biochemical and growth responses of silver maple (Acer saccharinum L.) to sodium chloride and calcium chloride - Jacek Patykowski; Jeremi Kołodziejek; Mateusz Wala (PeerJ, 2018)
The present research investigated the response of silver maple (Acer saccharinum L.) to salt treatment. The short- and long-term effects of NaCl and CaCl2 treatments on plant fitness characteristics (growth parameters, leaf chlorophyll content) and biochemical stress-coping mechanisms (proline accumulation as well as enzymatic activities) were examined. We found that the silver maple response to salt stress strictly depended on salt type and dose—calcium chloride was less toxic than sodium chloride, but high concentrations of both salts negatively influenced plant growth. The accumulation of proline, slight changes in the activity of superoxide dismutase and marked changes in catalase and peroxidase activities in the roots and leaves indicated complexity of the plant response. It was also shown that after one year, enzymatic parameters were restabilized, which indicates plant recovery, but the reduced mass of seedlings suggests that one year is not enough to cope with the prolonged cyclic salt stress, both resulting from NaCl and CaCl2 application. Therefore, seedlings of silver maple should be considered as moderately susceptible to salinity. Hence, it is recommended to use silver maple on non-de-iced urban areas, while planting on often de-iced roads should be avoided.